KL-6 Mucin as Serum Tumor Marker of Metastatic Renal Cancer: A Case Report - Kyohei Ishida; Go Hasegawa; Toshinori Takada; Akira Ogose; Gen Kawaguchi; Yohei Ikeda; Hiroki Nishiyama; Noboru Hara; Tsutomu Nishiyama (Case Reports in Urology)
We encountered a case of metastatic renal cell carcinoma in which the serum level of KL-6, a therapeutic marker, was exceptionally high and fluctuated with the progression of treatment. A 74-year-old man was diagnosed with right renal cystic cancer and multiple metastases in October 2022. The KL-6 level was 27490 U/mL. He started treatment with lenvatinib and pembrolizumab. KL-6 decreased to 3885 U/mg in February 2023. The patient’s proteinuria worsened, leading to the discontinuation of lenvatinib. KL-6 increased to 25950 U/mL in April. He discontinued pembrolizumab and started taking cabozantinib. In September, drug-induced bilateral inflammatory pneumonitis developed. He discontinued cabozantinb and began taking axitinib. KL-6 decreased; however, he suffered from severe diarrhea and subsequent renal insufficiency. He discontinued axitinib in November. KL-6 increased to 29640 U/mL in December.